TNF Blockade Maintains an IL-10+ Phenotype in Human Effector CD4+ and CD8+ T Cells - Roberts, Ceri A.; Durham, Lucy E.; Fleskens, Veerle; Evans, Hayley G.; Taams, Leonie S. (Frontiers in Immunology, 2017)
CD4+ and CD8+ effector T cell subpopulations can display regulatory potential characterized by expression of the prototypically anti-inflammatory cytokine IL-10. However, the underlying cellular mechanisms that regulate expression of IL-10 in different T cell subpopulations are not yet fully elucidated. We recently showed that TNF inhibitors (TNFi) promote IL-10 expression in human CD4+ T cells, including IL-17+ CD4+ T cells. Here we further characterized the regulation of IL-10 expression via blockade of TNF signaling, or other cytokine/co-stimulatory pathways, in human T cell subpopulations. Addition of the TNFi drug adalimumab to anti-CD3-stimulated human CD4+ T cell/monocyte co-cultures led to increased percentages of IL-10+ cells in pro-inflammatory IL-17+, IFNγ+, TNFα+, GM-CSF+ and IL-4+ CD4+ T cell subpopulations. Conversely, exogenous TNFα strongly decreased IL-10+ cell frequencies. TNF blockade also regulated IL-10 expression in CD4+ T cells upon antigenic stimulation. Using time-course experiments in whole PBMC cultures, we show that TNF blockade maintained, rather than increased, IL-10+ cell frequencies in both CD4+ and CD8+ T cells following in vitro stimulation in a dose- and time-dependent manner. Blockade of IL-17, IFNγ, IL-6R or CD80/CD86-mediated co-stimulation did not significantly regulate IL-10 expression within CD4+ or CD8+ T cell subpopulations. We show that TNF blockade acts directly on effector CD4+ T cells, in the absence of monocytes or CD4+CD25highCD127low regulatory T cells and independently of IL-27, resulting in higher IL-10+ frequencies after 3 days in culture. IL-10/IL-10R blockade reduced the frequency of IL-10-expressing cells both in the presence and absence of TNF blockade. Addition of recombinant IL-10 alone was insufficient to drive an increase in IL-10+ CD4+ T cell frequencies in 3 day CD4+ T cell/monocyte co-cultures, but resulted in increased IL-10 expression at later time points in whole PBMC cultures. Together these data provide additional insights into the regulation of IL-10 expression in human T cells by TNF blockade. The maintenance of an IL-10+ phenotype across a broad range of effector T cell subsets may represent an underappreciated mechanism of action underlying this widely used therapeutic strategy.